2023
DOI: 10.2106/jbjs.23.00195
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant Unstable and Stable Gravity Stress Tests on Weight-Bearing Stable Weber B Ankle Fractures Treated Nonoperatively

Abstract: Background: Replacing gravity stress tests with weight-bearing radiographs to evaluate the stability of Weber B (also called Lauge-Hansen supination-external rotation [SER]) ankle fractures results in a lower surgery rate, thus avoiding associated risks and complications. Still, nonoperative treatment of weight-bearing stable fractures is controversial because of the scarcity of strong evidence. We investigated the influence of a concomitant unstable gravity stress test compared with a stable gravi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…In a Level II prospective study, Gregersen et al 15 performed a noninferiority study of 149 Weber B ankle fractures deemed to be stable on weightbearing radiographs, treated with functional orthoses and early weightbearing. The authors found that those patients with a concurrent gravity stress test considered unstable (indicating a partial deltoid ligament rupture) did not have unfavorable outcomes at 2-year follow-up when compared with those with a stable gravity stress test.…”
Section: Ankle Fracturesmentioning
confidence: 99%
“…In a Level II prospective study, Gregersen et al 15 performed a noninferiority study of 149 Weber B ankle fractures deemed to be stable on weightbearing radiographs, treated with functional orthoses and early weightbearing. The authors found that those patients with a concurrent gravity stress test considered unstable (indicating a partial deltoid ligament rupture) did not have unfavorable outcomes at 2-year follow-up when compared with those with a stable gravity stress test.…”
Section: Ankle Fracturesmentioning
confidence: 99%
“…A difference of 7.5 MOxFQ points constitutes our noninferiority limit. Based on preliminary results from another study conducted on ankle fractures at our hospital, 24 we used a standard deviation (SD) of 12 points MOxFQ score. To detect a mean difference in MOxFQ score of 7.5 points (SD 12) at two years with a significance level of 5% and power of 90% with equal allocation to two arms will require 44 patients in each arm of the trial.…”
Section: Secondary Outcomesmentioning
confidence: 99%
“…12 Other studies have suggested that fractures that are stable on weightbearing radiographs (SER2 and SER4a) can be treated nonoperatively with satisfactory short-and midterm results. 3,[5][6][7][8]11,13,14 We defined ankle stability as the joint's ability to remain anatomically aligned in the presence of deforming forces. Two recent biomechanical studies support the nonoperative treatment of SER4a fractures.…”
Section: Introductionmentioning
confidence: 99%
“…However, understanding ankle fractures with concomitant deltoid ligament injuries has evolved. 4 - 6 The traditional binary understanding of stability, either as stable or unstable, has been challenged by clinical and biomechanical findings indicating that partial deltoid ligament injuries, where the deep posterior tibiotalar ligament (dPTTL) remains intact, are common. 2 , 4 - 6 , 9 It has been proposed to classify such injuries as SER4a.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation